1996
DOI: 10.1037/0278-6133.15.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the monitoring process model to coping with severe long-term medical threats.

Abstract: Guided by the monitoring process model (MPM), the authors explored the illness responses of 2 samples: high monitors (who are cognitively vigilant to and amplify threat-related cues) and low monitors (who avoid them and blunt their impact). Both samples-101 women with human papillomavirus-related precancerous cervical dysplasia and 75 HIV-infected gay men-were undergoing long-term medical follow-up and management. Structural equation analysis showed an adequate fit of the MPM to the data within each sample, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
93
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 74 publications
13
93
0
1
Order By: Relevance
“…Monitoring was unrelated to depressive symptoms, adding to previous findings associating monitoring with anxiety but not with depression [45,57]. Our findings also demonstrated that while high monitors who received positive or indeterminate test results experienced greater distress, those who were non-carriers were not more distressed than low monitors.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Monitoring was unrelated to depressive symptoms, adding to previous findings associating monitoring with anxiety but not with depression [45,57]. Our findings also demonstrated that while high monitors who received positive or indeterminate test results experienced greater distress, those who were non-carriers were not more distressed than low monitors.…”
Section: Discussionsupporting
confidence: 79%
“…Similar monitoring  test result interactions were obtained among women undergoing trans-vaginal ultrasound: high monitors responded only to an abnormal test result with elevated distress [58]. These findings are also consistent with predictions of the Monitoring Process Model [36,45], whereby high monitors' distress is activated only when threatened with an aversive event and is not present when stress is low or absent. This results from their tendency to perceive personal risks as higher; to experience more intrusive ideation; and to encode threats as catastrophic [34,37,41,43,44,59,60].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…12,13 In response to cervical cancer risk feedback and other health stressors, patients considered high monitors tend to respond with heightened and more sustained perceived vulnerability, greater negative expectations about their health, less satisfaction with health-related information, more disease-specific distress and physiologic arousal, and diminished selfefficacy regarding their ability to cope with the health threat. This pattern of response to diagnostic feedback can lead to intrusive ideation that triggers avoidant thoughts and behaviors, which ultimately may be detrimental to health behaviors and adherence over the long term, 14,15 particularly when less information and support are available. Patients considered low monitors (blunters) are more likely to ignore and psychologically distance themselves from cancer threats and tend to be less distressed in the face of diagnostic feedback, particularly when not presented with voluminous information, but they also are less adherent from the onset.…”
Section: Early Detection Of Cervical Cancer: Adherence To Screening Amentioning
confidence: 99%
“…Yet, little is currently known about women's knowledge and practice of precautionary behaviors to prevent or lessen the impact of this condition (Coward, 1999;Clark, Wasilewska, et al, 1997). Guided by the Cognitive-Social Health Information Processing (C-SHIP) model (Miller, Shoda, et al, 1996;Miller & Rodoletz, 1996;Miller & Diefenbach, 1998), the overarching objective of the present study is to explore the cognitive-affective factors associated with knowledge about LE symptom-minimization practices, their initiation, and the sustained maintenance of these practices among breast cancer survivors currently unaffected by LE.…”
Section: Introductionmentioning
confidence: 99%